A TERTIARY HOSPITAL RESEARCH ON OVER WEIGHT/OBESE DIABETIC CONSEQUENCES. A CROSS-SECTIONAL INVESTIGATION. - Kumar, Amit (Student’s Journal of Health Research Africa, 2023)
Introduction: The prevalence of diabetes mellitus has exhibited a notable surge in recent decades, mirroring the concerning trend observed in obesity rates. Of particular concern is the escalating incidence of type 2 diabetes mellitus among paediatric populations, which has witnessed a twofold increase. Aim: This study aimed to investigate the prevalence of obesity and diabetic complications among diabetic patients in India. Methods: A cross-sectional investigation was conducted utilising an established clinical registry within the confines of a tertiary care facility over a span of 18 months. A retrospective analysis was conducted on the medical records of adult individuals diagnosed with type 2 diabetes mellitus. Results: The study included 495 people with a 10.5% HbA1c. 91% (n=451) of 495 patients were obese/overweight. 37.8% (n=187) of diabetics aged 50–59, and 59% (n=292) have had diabetes for less than 10 years. 29.9% (n=148) had one additional comorbidity (hypertension or dyslipidemia), while 63.4% (n=314) had two. The prevalence of complications was 18.9% (n=94) myocardial infarction, 11.1% (n=55) stroke, and 9% (n=45) CKD. Age and hypertension were significantly associated with diabetic complications (adjusted OR=1.03; 95% CI 1.00 to 1.07; p=0.041 and OR=4.06; 95% CI 1.21 to 13.60; p=0.023). Conclusion: In our research, it appears that a body mass index (BMI) exceeding 23 kg/m 2, which is indicative of obesity or overweight, does not exhibit a significant correlation with the occurrence of complications. Advanced age and the presence of hypertension, conversely, demonstrate robust prognostic value in predicting the occurrence of complications. Recommendation: Given the current understanding of diabetes, it is advisable to promote public education targeting the affected population in order to mitigate the associated complications.